2011
DOI: 10.1097/pcc.0b013e31820ac42a
|View full text |Cite
|
Sign up to set email alerts
|

Serratia marcescens outbreak in a neonatal intensive care unit related to the exit port of an oscillator

Abstract: Implementation and adherence to infection control measures is essential to prevent transmission of opportunistic pathogens among ventilated infants. Oscillators can generate droplets that travel farther than 1 m from the source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
3
9
0
1
Order By: Relevance
“…Outbreaks in NICUs caused by Serratia spp. have been reported in the literature (13). In our study, non-fermentative bacteria were found to be the third leading causative agent after Enterobacteriaceae.…”
Section: Discussionsupporting
confidence: 51%
“…Outbreaks in NICUs caused by Serratia spp. have been reported in the literature (13). In our study, non-fermentative bacteria were found to be the third leading causative agent after Enterobacteriaceae.…”
Section: Discussionsupporting
confidence: 51%
“…However, in other studies S. marcescens could not be detected among pathogens isolated from cases of neonatal sepsis [25, 31, 39]. In the last decade, several outbreaks in NICU were documented [5658], causing potentially fatal sepsis, meningitis, or pneumonitis in very premature or low birth weight neonates with high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Die Verwendung einer anderen Mineralwassermarke beendete den Ausbruch. Bei der Ausbruchsuntersuchung von Yapicioglu et al [34] Interessant an der Untersuchung von MacDonald et al [26] ist nicht nur die besondere Quelle des Serratia-Isolates (HFO-Beatmungsgerät, Auslassventil), sondern auch das systematische proaktive Vorgehen des Ausbruchsmanagementteams, das die infektionsepidemiologische Relevanz von S. marcescens für NICU-Patienten frühzeitig erkannt hat [42]. Die Autoren verweisen darauf, dass Hygienerisiken beim Einsatz der HFOBeatmung durchaus beschrieben sind [43], jedoch nicht in ausreichendem Ausmaß zur Implementierung zusätzlicher Schutzmaßnahmen geführt haben.…”
Section: Ausbruchsuntersuchung Und Maßnahmen Zur Ausbruchskontrolleunclassified